2021
DOI: 10.3390/ijms22169033
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Inflammation in Endometriosis: Improving Knowledge for Development of New Pharmacological Strategies

Abstract: According to a rich body of literature, immune cell dysfunctions, both locally and systemically, and an inflammatory environment characterize all forms of endometriosis. Alterations in transcripts and proteins involved in the recruitment of immune cells, in the interaction between cytokines and their receptors, cellular adhesion and apoptosis have been demonstrated in endometriotic lesions. The objective of this narrative review is to provide an overview of the components and mechanisms at the intersection bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 110 publications
(125 reference statements)
0
33
0
Order By: Relevance
“…Previous bulk RNAseq and microarray analyses revealed altered transcriptomic profiles in the eutopic endometrium of women with versus without endometriosis ( 3 5 ). With disease, the eutopic endometrium displays a pro-inflammatory transcriptomic feature and fails to elicit normal steroid hormone responses that are essential for endometrial transformation ( 4 , 6 8 ). This pro-inflammatory feature was also observed in the microarray and RNAseq profiles of isolated endometrial stromal fibroblasts (eSFs), mesenchymal stem cells (eMSCs), and macrophages ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous bulk RNAseq and microarray analyses revealed altered transcriptomic profiles in the eutopic endometrium of women with versus without endometriosis ( 3 5 ). With disease, the eutopic endometrium displays a pro-inflammatory transcriptomic feature and fails to elicit normal steroid hormone responses that are essential for endometrial transformation ( 4 , 6 8 ). This pro-inflammatory feature was also observed in the microarray and RNAseq profiles of isolated endometrial stromal fibroblasts (eSFs), mesenchymal stem cells (eMSCs), and macrophages ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of endometrial cells in an ectopic location causes a natural response of innate and adaptive immune system components, which try to eliminate menstrual debris and initiate tissue repair. However, the inability to deal with the persistent presence of menstrual debris over time may lead to immune system overload and subsequent immune alterations [27]. This can aggravate the inflammatory process and transform it into a chronic state.…”
Section: Discussionmentioning
confidence: 99%
“…First, previous studies have shown that inflammation is the central process in EMT, which can lead to pain, fibrosis, adhesion formation, and infertility ( 2 , 27 ). Inflammation plays an important role in the etiology and pathophysiology of EMT ( 28 , 29 ). Furthermore, ApoE-ϵ4 is reportedly associated with higher levels of inflammation ( 18 ).…”
Section: Discussionmentioning
confidence: 99%